Identification and Expression of Secreted In Xylem Pathogenicity Genes in Fusarium oxysporum f. sp. pisi - Jenkins, Sascha; Taylor, Andrew; Jackson, Alison C.; Armitage, Andrew D.; Bates, Helen J.; Mead, Andrew; Harrison, Richard J.; Clarkson, John P. (Frontiers in Microbiology, 2021)
Fusarium oxysporum is a soilborne fungal plant pathogen responsible for causing disease in many economically important crops with ‘special forms’ (formae speciales) adapted to infect specific plant hosts. F. oxysporum f. sp. pisi (FOP) is the causal agent of Fusarium wilt disease of pea and has been reported in every country where peas are grown commercially. Disease is generally controlled using resistant cultivars possessing single major gene resistance and therefore there is a constant risk of breakdown. The main aim of this work was to characterise F. oxysporum isolates collected from diseased peas in the UK as well FOP isolates obtained from other researchers representing different races through sequencing of a housekeeping gene and the presence of Secreted In Xylem (SIX) genes, which have previously been associated with pathogenicity in other F. oxysporum f. spp. F. oxysporum isolates from diseased UK pea plants possessed none or just one or two known SIX genes with no consistent pattern of presence / absence, leading to the conclusion that they were foot-rot causing isolates rather than FOP. In contrast, FOP isolates had different complements of SIX genes with all those identified as race 1 containing SIX1, SIX6, SIX7, SIX9, SIX10, SIX11, SIX12 and SIX14. FOP isolates that were identified as belonging to race 2 through testing on differential pea cultivars, contained either SIX1, SIX6, SIX9, SIX13, SIX14 or SIX1, SIX6, SIX13. Significant upregulation of SIX genes was also observed in planta over the early stages of infection by different FOP races in pea roots. Race specific SIX gene profiling may therefore provide potential targets for molecular identification of FOP races but further research is needed to determine whether variation in complement of SIX genes in FOP race 2 isolates results in differences in virulence across a broader set of pea differential cultivars.